Industrially scalable and cost-effective Mn2+ doped ZnxCd1−xS/ZnS nanocrystals with 70% photoluminescence quantum yield, as efficient down-shifting materials in photovoltaics. Issue 3 (14th January 2016) - Levchuk, I.; Würth, C.; Krause, F.; Osvet, A.; Batentschuk, M.; Resch-Genger, U.; Kolbeck, C.; Herre, P.; Steinrück, H. P.; Peukert, W.; Brabec, C. J.
Abstract : We present colloidally stable and highly luminescent Zn x Cd1– x S:Mn/ZnS core–shell nanocrystals (NCs) as cost-effective light converters for silicon photovoltaic (PV). Abstract : We present colloidally stable and highly luminescent Zn x Cd1− x S:Mn/ZnS core–shell nanocrystals (NCs) synthesized via a simple non-injection one-pot, two-step synthetic route, which can be easily upscaled. A systematic variation of the reaction component, parameters and thickness of the ZnS shell yielded doped nanocrystals with a very high photoluminescence quantum yield ( Φ pl ) of 70%, which is the highest value yet reported for these Mn-doped sulfide-semiconductor NCs. These materials can be synthesized with high reproducibility in large quantities of the same high quality, i.e., the same Φ pl using accordingly optimized reaction conditions. The application of these zero-reabsorption high quality NCs in the light conversion layers, deposited on top of a commercial monocrystalline silicon (mono-Si) solar cell, led to a significant enhancement of the external quantum efficiency (EQE) of this device in the ultraviolet spectral region between 300 and 400 nm up to ca. 12%. EQE enhancement is reflected by an increase in the power conversion efficiency (PCE) by nearly 0.5 percentage points and approached the theoretical limit (0.6%) expected from down-shifting for this Si solar cell. The resulting PCE may result in a BoM (bill of materials) cost reduction of app. 3% for mono-Si photovoltaic modules. Such small but distinct improvements are expected to pave the road for an industrial application of doped semiconductor NCs as cost-effective light converters for silicon photovoltaic (PV) and other optoelectronic applications.